Inward and outward internationalization in Malaysian Small-Medium Enterprises (SMEs): a learning approach. - Nur Izzati Mohamad Anuar (2018)
This thesis investigates the learning processes of internationalizing small and medium enterprises (SMEs) that engage in inward internationalization (international sourcing),and outward internationalization (export).Although the notions of knowledge and learning are well addressed in the literature of internationalization,research on international sourcing from the perspectives of knowledge and learning,as well as research on the connections between international sourcing and export associated with knowledge and learning require serious attention.This research attempts to address this apparent theoretical and empirical deficiencies by providing a deeper understanding on the learning processes associated with international sourcing,export,and connections between international sourcing and export.Based on knowledge-based theories,organizational learning theories,and internationalization theories underpinned by the concept of cross-border buyer-supplier relationship,this research examines 1) the acquisition and exploitation of new knowledge from direct experience in international sourcing,and imitation of key foreign supplier, 2) the acquisition and exploitation of new knowledge from direct experience in export,and imitation of key foreign buyer, and 3) the acquisition,distribution, and exploitation of relevant knowledge by associating inward and outward internationalization.Thus,this research adopts a qualitative case study approach based on 10 case studies of the internationalizing SMEs in Malaysia.Semi-structured interviews with the Managing Director of case firms were conducted over a two-year period.Additionally,participant observations were conducted by attending the meetings related to import-export activities and documentations were gathered for data triangulation.The findings of this research contribute and extend the growing body of research on the importance of knowledge and learning on the internationalization of firm by developing conceptual framework of holistic view of internationalization which embrace inward and outward internationalization in terms of knowledge acquisition and exploitation,and the connections between inward and outward internationalization in terms of knowledge acquisition, distribution, and exploitation.Close relationship with key foreign suppliers empowered the imitation of key foreign suppliers of internationalization and technological knowledge.It also empowered firms to connect inward to outward internationalization through collaborative knowledge sharing.The distribution of knowledge through tacit-tacit and tacit-explicit knowledge sharing underpinned by formal planning was a perquisite for inward-outward internationalization connections to be established by those firms.